Affective Moments in the Films of Martel, Carri, and Puenzo - Selimović, Inela (Palgrave Macmillan UK, 2018)
This book studies the intimate tensions between affect and emotions as terrains of sociopolitical significance in the cinema of Lucrecia Martel, Albertina Carri, and Lucía Puenzo. Such tensions, Selimović argues, result in "affective moments" that relate to the films' core arguments. They also signal these filmmakers' novel insights on complex manifestations of memory, desire, and violence. The chapters explore how the presence of pronounced-but reticent-affect complicates emotional bonding in the everydayness depicted in these films. By bringing out moments of affect in these filmmakers' diegetic worlds, this book traces the ways in which subtle foci on gender, class, race, and sexuality correlate in these Argentine women's films.